Palatosquisis en un ternero raza Holstein. Caso clínico - Centellas Jáuregui, Rosita Valeria (2024)
Palatoschisis is a hereditary teratoma that occurs in cattle, it is a hereditary anomaly that affects the oral cavity due to a bad closure during embryonic development, this malformation can have a negative impact on the animal, affecting its feeding and generating problems such as regurgitation and rhinitis. We report the case of a 2-month-old female bovine that presented a malformation specifically in the hard palate. It was observed that the calf presented palatoschisis, showed difficulty in feeding, as well as rhinitis, symptoms derived from the described anomaly.